2018
DOI: 10.1093/ije/dyy095
|View full text |Cite
|
Sign up to set email alerts
|

Population mobility reductions associated with travel restrictions during the Ebola epidemic in Sierra Leone: use of mobile phone data

Abstract: BackgroundTravel restrictions were implemented on an unprecedented scale in 2015 in Sierra Leone to contain and eliminate Ebola virus disease. However, the impact of epidemic travel restrictions on mobility itself remains difficult to measure with traditional methods. New ‘big data’ approaches using mobile phone data can provide, in near real-time, the type of information needed to guide and evaluate control measures.MethodsWe analysed anonymous mobile phone call detail records (CDRs) from a leading operator i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 30 publications
(29 reference statements)
5
97
0
Order By: Relevance
“…However, instead of being based on the probability of observing a system in a particular state, it utilizes the frequency of discrete motifs, i.e symbols, associated with the growth, decay, and stasis of a time series. For example, in a binary time series the permutation entropy in two dimensions would count the frequency of the set of possible ordered pairs, {[01], [10]}, and the Shannon entropy, or uniformity, of this distribution is the permutation entropy. In higher dimensions, one can define an alphabet of symbols over all factorial combinations of orderings in a given dimension, e.g., {[0, 1, 2], [2,1,0], [1,0,2], etc.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, instead of being based on the probability of observing a system in a particular state, it utilizes the frequency of discrete motifs, i.e symbols, associated with the growth, decay, and stasis of a time series. For example, in a binary time series the permutation entropy in two dimensions would count the frequency of the set of possible ordered pairs, {[01], [10]}, and the Shannon entropy, or uniformity, of this distribution is the permutation entropy. In higher dimensions, one can define an alphabet of symbols over all factorial combinations of orderings in a given dimension, e.g., {[0, 1, 2], [2,1,0], [1,0,2], etc.…”
Section: Resultsmentioning
confidence: 99%
“…However, the predictions for SARS failed to match the data 3,5 . Over the subsequent 15 years, the scientific community developed a rich understanding for how social contact networks, variation in health-care infrastructure, the spatial distribution of prior immunity, etc., drive complex patterns of disease transmission [6][7][8][9][10][11] , and demonstrated that data-driven, dynamic, and or agentbased models can produce actionable forecasts [12][13][14][15][16][17] . Additionally, studies have demonstrated that predicting different components of outbreaks-e.g., the expected number of cases, pace, and tempo of cases needing treatment, demand for prophylactic equipment, importation probability, etc.-is feasible 3,13,[18][19][20][21][22][23][24] .…”
mentioning
confidence: 99%
“…For example, a study published in 2019 combined epidemiological surveillance data, travel surveys, parasite genetics and anonymized mobile phone data to measure the spread of malaria parasites in southeast Bangladesh 92 . A retrospective analysis of mobile phone call data in Sierra Leone from 2015 showed how it might have been used to assess the impact of travel restrictions on mobility during the Ebola epidemic 46 .…”
Section: Precision Public Healthmentioning
confidence: 99%
“…To date, mobile-derived human mobility, especially using CDRs, have been used to explore the transmission of malaria, 12,31,55 dengue, 29 cholera, 63 measles, 64 rubella, 28 Ebola, 65,66 and HIV infection. 67 Taking malaria as an example, we illustrate how spatiotemporally explicit mobility derived from mobile positioning data has been used to define malaria connectivity and inform interventions.…”
Section: Mobile-derived Human Movements and Disease Connectivitymentioning
confidence: 99%